The implementation of Zakatnomics To Improve The Prosperity of Zakat Recipients (Mustahik) in the City of Makassar - Jamaluddin,; Baharuddin Semmaila,; Andi Sumardin, (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
This study aims to reveal another side of the utilization of zakat through the concept of zakatnomics. Zakatnomics is a combination of zakat and economics. This concept is based on four pillars, namely; religious spirit, productive culture, economic justice, zakat institutions, infaq, alms and waqf. In short, zakatnomics has two welfare motivations, spiritual and material welfare which are human needs in the world. This study is qualitative and uses informant data sources. The results of this study indicate that the religious spirit of mustahik who receive zakat funds can be said to be good or increasing. In contrast, in the productive culture category, it has not increased effectively because the results of the productive efforts carried out only cover daily needs. The pillar of economic justice has been implemented well by mustahik where the profits obtained are distributed to meet all family needs. Likewise, the institutional category of zakat, can be said to have run well, although it is necessary to improve services and carry out socialization on an ongoing basis.